Design and Development of a User-Friendly Motorized Apparatus for the Filling of Portable Infusion Pumps by Hospital and Homecare Health Workers - Bourget Philippe; Amin Alexandre; Loeuillet Richard; De Almeida Tavares Laura Simoes; Violain Cendrine; Thromas Nathalie; Dupont Christian; Gohier Eric (De Gruyter, 2016)
Purpose: Musculoskeletal disorders (MSD) remain the most common occupational disease in the Western countries. Beside the effects on workers themselves, MSDs may lead to high costs to enterprises and the society as a whole. Among the painful or tiring positions encountered in healthcare settings, caregivers often cite the filling of portable infusion pumps (PIP). This context was conducive to achievement of the goal of the following project: the development of a motorized apparatus designed to minimize the risk of MSDs caused by repeated gestures of filling PIPs.